PENGARUH PERSEPSI RISIKO, PRICE CONSCIOUSNESS, FAMILIARITY, PERSEPSI KUALITAS, DAN CITRA TOKO PADA MINAT BELI KONSUMEN - Santoso, Dharmawan; Najib, Mukhamad; Munandar, Jono Mintarto (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
This research aims to identify the difference of the latent variables (shelf space, familiarity, perceived risk, price consciousness, citra private label, kualitas servis, and perceived quality) among ritel industries; to analyze the influence among latent variables; and to analyze the effect of perceived risk, price cosnciousness, familiarity, perceived quality, and store image on consumer purchase intention on food private label. This research involved 274 respondent consist of hypermarket, supermarket and minimarket consumer in Bogor city that were chosen by quota sampling method. Mann Whitney test and CB-SEM were used in data analysis, with confidence level is 95,0 percent. The results showed that store image, perceived risk, kualitas servis, familiarity, perceived quality and puchase intention have differentiation among hypermarket, supermarket and minimarket consumer. Moreover, the result also found that shelf space influenced familiarity and perceived quality; kualitas servis influenced citra private label, and citra private label and familiarity influenced perceived risk. The result also revealed a significant influence of store image on purchase intention.